Air pollution, athletic health and performance at the Olympic Games - Fitch, K. (The Journal of Sports Medicine and Physical Fitness, 2016)
The objective of this study was to briefly review air pollution and its effects on athletes' health and performance and to examine air quality (AQ) at specific Olympic Summer Games between 1964 and 2008. It will focus on any attempts made by the cities hosting these Olympics to improve AQ for the Games and if undertaken, how successful these were. The author had a medical role at five of the seven Olympic Games that will be examined and hence has personal experiences. Information was obtained from the readily accessible official reports of the Olympic Games, relevant published papers and books and the internet. For each of these seven Olympic Games, monitoring AQ was far below current acceptable standards and for the majority, minimal or no data on major pollutants was available. From what can be ascertained, at these Games, AQ varied but was less than optimal in most if not all. Nevertheless, there were few reported or known unfavorable effects on the health of Olympic athletes. To date, there have been few reported consequences of sub-optimal AQ at Olympic Games. The focus on AQ at Olympic Games has gradually increased over the past five decades and is expected to continue into the future.